SYNTHESIS AND CHARACTERIZATION OF ACTIVATED CARBON PREPARED FROM RICE HUSK BY PHYSICS-CHEMICAL ACTIVATION - Suyoga Wiguna, Anak Agung Gde; Mardana, Ida Bagus Putu; Artawan, Putu (Universitas Mataram, 2024)
Activated carbon is an amorphous carbon material predominantly composed of free carbon atoms with high adsorption capacity. The amorphous structure in activated carbon affects its adsorption capacity; the higher the percentage of amorphous carbon, the greater the adsorption capacity of the activated carbon. Activated carbon can be obtained from rice husk waste containing 30-40% C in cellulose, hemicellulose, and lignin. Therefore, this study was conducted to observe activated carbon's phases, morphology, elemental composition, and particle size. Activated carbon was synthesized using a physics-chemical activation method, which began with washing the rice husk samples, followed by air drying, carbonizing into charcoal, and grinding it finely. The rice husk charcoal powder was then physically activated at a temperature of 500â„ƒ. The physically activated product was then chemically activated using 6M HCl with a charcoal-to-activator ratio of 1:10 (m/V), stirred at 250 rpm for 1 hour, and then allowed to settle for 24 hours. It was then washed and dried to produce activated carbon powder. XRD test results showed diffraction peaks at 2Î¸ = 22.23Â° without sharp or pointed peaks, indicating that the activated carbon has an amorphous structure. SEM test results showed the morphology of rice husk-activated carbon with spherical particle shapes and a particle size distribution of 20-70 nm. EDX test results showed that the rice husk activated carbon is predominantly composed of C, O, and Si with respective percentages of 54.31%, 40.04%, and 2.49%. Â